Analisis terhadap Penetapan Pengadilan Agama Cibinong tentang Dispensasi Pernikahan di Bawah Umur - M Fajrin; Suyudi Arif; Yono Yono (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Marriage is one thing that is taken seriously, which results in a person being bound for life with his partner. Therefore, marriage requires careful preparation, namely physical maturity and mental maturity. Basically, it is the maturity of the soul that is very meaningful to enter the household gate. Married at a young age when a person is not physically or mentally ready often causes problems later in life. Even though the law has regulated the age limit for marriage, in practice, there are still underage marriages that can be carried out under certain conditions, namely when notifying the KUA by attaching a marriage dispensation. So that marriage is not only legal according to religion, but also legal according to the state. If the marriage is not accompanied by a marriage dispensation, then the marriage cannot be registered.